The genetic association with athlete status, physical performance, and injury risk in soccer - Murtagh, C. F.; Hall, E. C. R.; Brownlee, T. E.; Drust, B.; Williams, A. G.; Erskine, R. M. (International Journal of Sports Medicine, 2023)
The aim of this review was to critically appraise the literature concerning the genetic association with athlete status, physical performance, and injury risk in soccer. The objectives were to provide guidance on which genetic markers could potentially be used as part of future practice in soccer and to provide direction for future research in this area. The most compelling evidence identified six genetic polymorphisms to be associated with soccer athlete status (ACE I/D; ACTN3 rs1815739; AGT rs699; MCT1 rs1049434; NOS3 rs2070744; PPARA rs4253778), six with physical performance (ACTN3 rs1815739; AMPD1 rs17602729; BDNF rs6265; COL2A1 rs2070739; COL5A1 rs12722; NOS3 rs2070744), and seven with injury risk (ACTN3 rs1815739; CCL2 rs2857656; COL1A1 rs1800012; COL5A1 rs12722; EMILIN1 rs2289360; IL6 rs1800795; MMP3 rs679620). As well as replication by independent groups, large-scale genome-wide association studies are required to identify new genetic markers. Future research should also investigate the physiological mechanisms associating these polymorphisms with specific phenotypes. Further, researchers should investigate the above associations in female and non-Caucasian soccer players, as almost all published studies have recruited male participants of European ancestry. Only after robust, independently replicated genetic data have been generated, can genetic testing be considered an additional tool to potentially inform future practice in soccer.